2013
DOI: 10.1038/jhh.2013.108
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with changes in retinal microcirculation after antihypertensive treatment

Abstract: We report the results of hypertensive treatment over retinal arteriole narrowing in a group of 189 hypertensive patients during a 6-month treatment programme for hypertension. These patients were included in an observational study under clinical practice conditions and analysed using digital photographs of the eye fundus with a previously described semiautomatic snakes method. We analysed the relation between blood pressure control and retinal microcirculation changes during the treatment. We included 189 hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…It is worth noting that AVR appears to be an independent risk factor for stroke. AVR may have a further useful application in relation to the observation that the AVR parameter may increase in response to antihypertensive treatment by modifying the retinal arteriole diameter, expressing an improvement in retinal microcirculation 53 . In this context, AVR may be a useful indicator as a therapeutic target capable of reflecting the effectiveness of antihypertensive drug treatment in controlling high BP values, PA included.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that AVR appears to be an independent risk factor for stroke. AVR may have a further useful application in relation to the observation that the AVR parameter may increase in response to antihypertensive treatment by modifying the retinal arteriole diameter, expressing an improvement in retinal microcirculation 53 . In this context, AVR may be a useful indicator as a therapeutic target capable of reflecting the effectiveness of antihypertensive drug treatment in controlling high BP values, PA included.…”
Section: Discussionmentioning
confidence: 99%
“…83 In addition, 6-12 months of BP treatment resulted in wider arteriolar diameters. 84,85 Finally, lifestyle interventions may also be a treatment option to normalize microvascular diameters. 86 Data on retinal microvascular diameters and renal function or disease are less consistent.…”
Section: Retinal Imagingmentioning
confidence: 99%
“…The architecture showed that the retinal venular area is larger than the retinal arteriolar area in fundus images, as expected based on previous findings obtained from vascular caliber measurements. 32,33 In addition, we elucidated as a novel finding that the correlation between the retinal arteriolar area and BP was stronger than that between manually evaluated AVR and BP.…”
Section: Discussionmentioning
confidence: 87%